2003
DOI: 10.1037/0096-1523.29.1.219
|View full text |Cite
|
Sign up to set email alerts
|

Estimating time to contact and impact velocity when catching an accelerating object with the hand.

Abstract: To catch a moving object with the hand requires precise coordination between visual information about the target's motion and the muscle activity necessary to prepare for the impact. A key question remains open as to if and how a human observer uses velocity and acceleration information when controlling muscles in anticipation of impact. Participants were asked to catch the moving end of a swinging counterweighted pendulum, and resulting muscle activities in the arm were measured. The authors also simulated mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 59 publications
2
21
0
3
Order By: Relevance
“…To do this, both TTA eff and TTC tgt need to be measured. It has been proposed that people do not perceptually estimate the exact TTA but, rather, a first-order approximation to the TTA defined by the current distance away divided by the speed of approach (D. N. Lee, 1998), a view supported by empirical data (see Senot et al, 2003;Tresilian, 1997). This approximation is often denoted t(d ), where d is the distance away (D. N. Lee, 1998).…”
Section: Meeting the Temporal Condition For Interception Using Continmentioning
confidence: 99%
See 1 more Smart Citation
“…To do this, both TTA eff and TTC tgt need to be measured. It has been proposed that people do not perceptually estimate the exact TTA but, rather, a first-order approximation to the TTA defined by the current distance away divided by the speed of approach (D. N. Lee, 1998), a view supported by empirical data (see Senot et al, 2003;Tresilian, 1997). This approximation is often denoted t(d ), where d is the distance away (D. N. Lee, 1998).…”
Section: Meeting the Temporal Condition For Interception Using Continmentioning
confidence: 99%
“…Thus, the temporal condition for hitting is that TTA eff ϭ TTC tgt . There will be some room for error, depending on the temporal accuracy constraints of the task (see Senot, Prevost, & McIntyre, 2003;Tresilian & Lonergan, 2002), as will be detailed later.…”
mentioning
confidence: 99%
“…Indeed, several psychophysical studies showed that the threshold of discrimination between an arbitrary accelerating (or decelerating) target and a constant speed target is generally high (for a review, see Zago et al 2009). Consistent with this poor perceptual sensitivity, the motor system does not seem to take into account unpredictable accelerations of a target in timing manual interceptions; instead, the latter are geared to target direction and speed (Engel and Soechting 2000;Port et al 1997;Senot et al 2003). Also, electrophysiological studies in the monkey showed that most neurons in a key visual-motion area, the middle temporal (MT) area, are tuned to direction and speed but not to acceleration, although an acceleration signal can be reconstructed from their population response (Lisberger and Movshon 1999;Price et al 2005;Schlack et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The subject then indicates a response at the moment of the object's speculated arrival time [Tresilian 1995;Benguigui et al 2003;Hecht et al 2002]. Another subset of coincidence-anticipation tasks is experiments involving interceptive action tasks, such as catching or hitting balls [Caljouw et al 2004;Senot et al 2003;Servos and Goodale 1998;Tresilian 1993]. The second class of experiments includes relative judgment tasks, in which subjects distinguish between two or more different values of TTC [Tresilian 1995;DeLucia and Novak 1997;Todd 1981].…”
Section: Ii1 Types Of Time-to-contact Experimentsmentioning
confidence: 99%